2013
DOI: 10.1590/s0100-67622013000600014
|View full text |Cite
|
Sign up to set email alerts
|

Emergência e qualidade de mudas de Enterolobium contortisiliquum (Vell.) Morong (Fabaceae) em diferentes substratos

Abstract: RESUMO -Este trabalho objetivou avaliar diferentes substratos na emergência e crescimento de mudas de Enterolobium contortisiliquum. Foram avaliadas composições a partir dos materiais vermiculita, moinha de carvão vegetal, subsolo, composto orgânico e serragem de madeira, totalizando 16 tratamentos. Durante 120 dias, avaliaram-se a emergência, o índice de velocidade e o tempo médio de emergência, a altura total da planta, o comprimento da raiz, o comprimento da parte aérea, o diâmetro do colo, o número de nódu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 19 publications
1
5
0
5
Order By: Relevance
“…The chemical analysis of the substrates allows to infer that there is a great availability of nutrients, mainly in the substrate S 2 , especially phosphorus (Table 1), where its limitation can result in restrictions on growth, especially during the initial phases (Gonçalves et al, 2013), since it is an integral component of important plant cell compounds, including phosphate-sugars, respiration and photosynthesis intermediates, as well as the phospholipids that make up plant membranes (Taiz & Zeiger, 2013). Despite this, it is worth mentioning that a dosage of 5g L -1 of the NPK fertilizer was added in all analyzed substrates, and no symptoms such as chlorosis and/or leaf necrosis were observed, which could evidence some type of phytotoxicity (Kratka & Correia, 2015) in any of the compositions simultaneously.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The chemical analysis of the substrates allows to infer that there is a great availability of nutrients, mainly in the substrate S 2 , especially phosphorus (Table 1), where its limitation can result in restrictions on growth, especially during the initial phases (Gonçalves et al, 2013), since it is an integral component of important plant cell compounds, including phosphate-sugars, respiration and photosynthesis intermediates, as well as the phospholipids that make up plant membranes (Taiz & Zeiger, 2013). Despite this, it is worth mentioning that a dosage of 5g L -1 of the NPK fertilizer was added in all analyzed substrates, and no symptoms such as chlorosis and/or leaf necrosis were observed, which could evidence some type of phytotoxicity (Kratka & Correia, 2015) in any of the compositions simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…According to Gonçalves et al (2013), substrates with greater porosity, but with moisture retention capacity preventing the rapid loss of water, can favor the emergence of seedlings. Araújo & Paiva Sobrinho (2011) also found that the IVE, the greatest growth of seedlings and the greatest expression of vigor, was provided by the presence of carbonized rice husks and vermiculite in the formation of their substrates.…”
Section: /8mentioning
confidence: 99%
See 1 more Smart Citation
“…Seigler & Ebinger, foram encontrados estudos na área de florística, fitossociologia (Barbosa et al, 2012;Ferreira et al, 2013;Costa et al, 2015) e sementes (Lima et al, 2017). E para Enterolobium contortisiliguum podem ser citados os estudos de Abreu et al (2015) (produção de mudas), Scalon et al (2006); Araújo & Paiva Sobrinho (2011); Barretto & Ferreira (2011); Gonçalves et al (2013) e Silva et al (2014) (substratos); e Melo et al (2008) e Lima et al (2010) (efeito do sombreamento no crescimento das mudas).…”
Section: Productivity Of Ministumps Of Three Forest Species In Differunclassified
“…Para produção de mudas, por exemplo, características consideradas essenciais para um bom substrato se referem a uma boa estrutura, boa porosidade e manutenção adequada da aeração junto ao sistema radicular, e ao mesmo tempo deve ser isento de substâncias tóxicas, inóculos de doenças e de plantas daninhas, insetos e sais em excesso (GONÇALVES et al, 2013). Entretanto, para produção de microgreens, no Brasil ainda não existem recomendações em relação aos diferentes substratos comerciais.…”
Section: Introductionunclassified